Cystic intracranial solitary fibrous tumor: a case report - Li, Yongzhe; Li, Dongxue; Yang, Li; Zhang, Jiaren; Gu, Xiaoyu; Song, Linfeng; Tian, Binlin; Li, Tingchao; Jiang, Lin (Frontiers in Oncology, 2024)
Solitary fibrous tumor (SFT) is a rare spindle cell tumor originating from mesenchymal tissue, and even rarer when it occurs intracranially. This case report described a 42-year-old man who presented with headache and limb weakness for more than 10 days. Magnetic resonance imaging (MRI) showed a well-defined multicompartmental cystic space-occupying lesion in the left occipital region, with surrounding edema and a compressed left lateral ventricle, the mass growing across the cerebellar vermis, which was initially diagnosed as hemangioblastoma. Neurosurgery was utilized to successfully remove the mass, and intracranial solitary fibrous tumor (ISFT) was identified by postoperative pathological analysis. Here, this article describes the imaging manifestations and pathologic features of a case of cystic intracranial solitary fibrous tumor, aiming to improve the understanding and diagnosis of this disease in order to provide an accurate therapy plan.